Dynamics of the fertilizer value chain in Mozambique - Zavale, H.; Matchaya, Greenwell C.; Vilissa, D.; Nhemachena, Charles; Nhlengethwa, Sibusiso; Wilson, D. (MDPI, 2020)
Mozambique is characterized by low agricultural productivity, which is associated with low use of yield-enhancing agricultural inputs. Fertilizer application rate averaged 5.7 kg ha-1 in Mozambique during the period 2006 to 2015, considerably low by regional targets, yet constraints that affect fertilizer use have not been thoroughly investigated. This study examined the constraints on fertilizer value chains in Mozambique to contribute to fertilizer supply chain strengthening. We used a combination of multivariate analysis and descriptive methods. Our findings indicate that fertilizer use has both demand and supply constraints. Key demand-side constraints include liquidity challenges, limited awareness about the benefits of using fertilizer, and low market participation, while the main supply-side constraints include high transaction costs, limited access to finance, and lack of soil testing results and corresponding fertilizer recommendations by soil type and crop uptake. These results suggest that scaling up the input subsidy program through vouchers (either paper-based vouchers or e-vouchers) with demonstration plots and effective targeting could drive up smallholders’ demand for fertilizer and fertilizer supply by strengthening a sustainable network of wholesalers and retailers. This would likely boost agricultural productivity.